Growth Factor Stimulation Regimes to Support the Development and Fusion of Cartilage Microtissues - Kelly, Daniel (My University, 2024)
Scaffold-free tissue engineering strategies using cellular aggregates, microtissues, or organoids as “biological building blocks” could potentially be used for the engineering of scaled-up articular cartilage or endochondral bone-forming grafts. Such approaches require large numbers of cells; however, little is known about how different chondrogenic growth factor stimulation regimes during cellular expansion and differentiation influence the capacity of cellular aggregates or microtissues to fuse and generate hyaline cartilage. In this study, human bone marrow mesenchymal stem/stromal cells (MSCs) were additionally stimulated with bone morphogenetic protein 2 (BMP-2) and/or transforming growth factor (TGF)-β1 during both monolayer expansion and subsequent chondrogenic differentiation in a microtissue format. MSCs displayed a higher proliferative potential when expanded in the presence of TGF-β1 or TGF-β1 and BMP-2. Next, the chondrogenic potential of these human MSCs was explored in a medium-high throughput microtissue system. After 3 weeks of culture, MSCs stimulated with BMP-2 during expansion and differentiation deposited higher levels of glycosaminoglycans (GAGs) and collagen, while staining negative for calcium deposits. The fusion capacity of the microtissues was not impacted by these different growth factor stimulation regimes. After 3 weeks of fusion, it was observed that MSCs stimulated with TGF-β1 during expansion and additionally with BMP-2 during chondrogenic differentiation deposited the highest levels of sulfated GAGs. No increase in type X collagen deposition was observed with additional growth factor stimulation. This study demonstrates the importance of carefully optimizing MSC expansion and differentiation conditions when developing modular tissue engineering strategies (e.g., cellular aggregates and microtissues) for cartilage tissue engineering applications.
Keywords: glycosaminoglycans (GAGs); Scaffold-free tissue engineering; microtissues; hyaline cartilage, osteoarthritis, spheroids, scaffold-free, growth factors, chondrogenesis; glycosaminoglycans (GAGs); Scaffold-free tissue engineering; microtissues